Small Bowel Resection Increases Paracellular Gut Barrier Permeability via Alterations of Tight Junction Complexes Mediated by Intestinal TLR4 - Courtney, Cathleen M. (J Surg Res, 2020)
BACKGROUND: Short bowel syndrome resulting from small bowel resection (SBR) is associated with significant morbidity and mortality. Many adverse sequelae including steatohepatitis and bacterial overgrowth are thought to be related to increased bacterial translocation, suggesting alterations in gut permeability. We hypothesized that after intestinal resection, the intestinal barrier is altered via toll-like receptor 4 (TLR4) signaling at the intestinal level. METHODS: B6 and intestinal-specific TLR4 knockout (iTLR4 KO) mice underwent 50% SBR or sham operation. Transcellular permeability was evaluated by measuring goblet cell associated antigen passages via two-photon microscopy. Fluorimetry and electron microscopy evaluation of tight junctions (TJ) were used to assess paracellular permeability. In parallel experiments, single-cell RNA sequencing measured expression of intestinal integral TJ proteins. Western blot and immunohistochemistry confirmed the results of the single-cell RNA sequencing. RESULTS: There were similar number of goblet cell associated antigen passages after both SBR and sham operation (4.5 versus 5.0, P > 0.05). Fluorescein isothiocyanate–dextran uptake into the serum after massive SBR was significantly increased compared with sham mice (2.13 ± 0.39 ng/μL versus 1.62 ± 0.23 ng/μL, P < 0.001). SBR mice demonstrated obscured TJ complexes on electron microscopy. Single-cell RNA sequencing revealed a decrease in TJ protein occludin (21%) after SBR (P < 0.05), confirmed with immunostaining and western blot analysis. The KO of iTLR4 mitigated the alterations in permeability after SBR. CONCLUSIONS: Permeability after SBR is increased via changes at the paracellular level. However, these alterations were prevented in iTLR4 mice. These findings suggest potential Intestinal barrier protein targets for restoring the intestinal barrier and obviating the adverse sequelae of short bowel syndrome.